The Influence of Employee Engagement and Work-Life Balance on Employee Performance through Satisfaction Work as Variables Mediation - Kusworo, Ahmad Dzulfikri Budi (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
Study This aim For analyze the influence of employee engagement and work-life balance on performance employee through satisfaction Work as variables mediation . Research use approach quantitative with method survey to employee company services in Indonesia. Research sample A total of 150 respondents were selected use purposive sampling technique . Data collected through questionnaire use five- point Likert scale . Data analysis techniques using multiple linear regression and mediation test . Variables independent in study This are employee engagement and work-life balance, meanwhile variables dependent is performance employees , with satisfaction Work as variables mediation . Research result expected show that employee engagement and work-life balance have influence positive to satisfaction work and performance employees . In addition , employee satisfaction Work estimated mediate connection between employee engagement and work-life balance towards performance employee . Study This give contribution theoretical development​ HR literature , especially related importance involvement employees and balance life Work in increase satisfaction work and performance . Studies latest show that work-life balance is often No impact directly on performance , but become significant when through satisfaction work and employee engagement.